Wetlands New Perspectives - Eyvaz, Murat; Albahnasawi, Ahmed (Environmental Sciences, 2023)
Wetlands are some of the most important ecosystems on our planet, providing a range of essential services from biodiversity conservation to water purification. Wetlands - New Perspectives is a comprehensive collection of seven chapters that presents the latest research and insights on wetlands from various perspectives. This book covers a range of topics, including the impacts of climate change on wetlands, the economic benefits of using wetlands for water retention, and the collaborative management of fire-resilient peatlands. It also provides insights into the prospects for the use of degraded wetlands and the management of prior converted hydric soils to support agriculture production. The authors of this book are experts in their fields and offer new perspectives on the management and conservation of wetlands. The book provides valuable insights and information for researchers, policymakers, and wetland managers who seek to promote the sustainable management of these vital ecosystems. Wetlands - New Perspectives is a must-read for anyone interested in the future of wetlands and the role they play in sustaining life on our planet. It is an essential resource for understanding the challenges and opportunities associated with the management and conservation of wetlands.